Physiotherapy and Rehabilitation Management of Musculoskeletal Affections in Canines - Ratnu, Devangini A.; Parikh, Pinesh V. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present work done on physiotherapy and rehabilitation techniques of locomotor system in canine practice is very meagre, especially on physical assessment and diagnostic findings of chronic complains of locomotor affections especially musculoskeletal in dogs with failed medical treatment and no surgical intervention was possible. Nine dogs (5 in the age group of >5 years, three of age group of 1 to 5 years, and one in the age group of <1 year) ;6, males and 3 females represented with affections of the musculoskeletal system were included in the present study, amongst which 3 cases were of hind quarter weakness and 6 cases of muscles strain, wherein physiotherapy was employed. All nine clinical cases were subjected to a detailed examination, including comprehensive neurological examination, diagnostic imaging, goniometry and haemato-biochemical estimations. All patients were treated with different types of physiotherapy modalities and rehabilitation techniques and observed the effectiveness of physiotherapy. Physiotherapy management of patients had early and optimal resumptions of functions. The rehabilitation modalities provided meritorious treatment options for symptomatic pain relief in patients, resulting in improved quality of life.